2009
DOI: 10.1097/pas.0b013e31818e6489
|View full text |Cite
|
Sign up to set email alerts
|

Low Stage Follicular Lymphoma: Biologic and Clinical Characterization According to Nodal or Extranodal Primary Origin

Abstract: Studies suggest that primary extranodal follicular lymphoma (FL) is not infrequent but it remains poorly characterized with variable histologic, molecular, and clinical outcome findings. We compared 27 extranodal FL to 44 nodal FL using morphologic, immunohistochemical, and molecular genetic techniques and evaluated the clinical outcome of these 2 similarly staged groups. Eight cases of primary cutaneous follicle center lymphoma were also studied. In comparison to nodal FL, a greater number of extranodal FL co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
28
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 31 publications
6
28
0
2
Order By: Relevance
“…The translocation reportedly was associated with a favorable prognosis with regard to OS and EFS, [23][24][25] was unrelated to prognosis, [26][27][28] and even was associated with a poor prognosis. 12,29,30 With regard to prognosis, we observed that t(14;18)/IGH-BCL2-positive patients had a lower CR rate and tended to have a poorer EFS than t(14;18)-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…The translocation reportedly was associated with a favorable prognosis with regard to OS and EFS, [23][24][25] was unrelated to prognosis, [26][27][28] and even was associated with a poor prognosis. 12,29,30 With regard to prognosis, we observed that t(14;18)/IGH-BCL2-positive patients had a lower CR rate and tended to have a poorer EFS than t(14;18)-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…The IGH/BCL2 rearrangement is a relatively specific molecular marker of FL, frequently used for diagnosis and monitoring of disease [2]. We have recently shown that the incidence of t(14;18) is significantly lower in limited stage FL and the status of t(14;18) appears to be predictive of clinical outcome [2]. Little is known of the molecular genetics of t(14;18)-negative FL or of the genetic differences between nodal and extranodal FL.…”
mentioning
confidence: 99%
“…The goal of the current study was to characterize stage I FL using high resolution array-based comparative genomic hybridization (aCGH). Validation of findings in aCGH were performed on 20 stage I FL as well as an additional 28 stage I and II FL cases by both RNA gene expression and DNA copy number.Twenty stage I FL were identified from the pathology database of Stanford University as previously described [2]. Agilent 60-mer oligonucleotide microarrays were used to analyze DNA copy number variations.…”
mentioning
confidence: 99%
See 2 more Smart Citations